The Development of Hadith Study Controversy in Indonesia: A Study of Miṣbāḥ al-Ẓulām by Muhajirin Amsar al-Dari - Fatihunnada Fatihunnada (Ulumuna, 2017)
There has been a wide presumption that hadith literature authored by Indonesian Muslim scholars is simple and static. This article challenges this view. It examines Miṣbāḥ al-Ẓulām, a commentary of Bulūg al-Marām, by Muhajirin Amsar al-Dari to show the dynamic development of the study on ikhtilāf al-ḥadīth (disputes over hadith). Grounded in the hermeneutic approach, this article argues that the development of hadith studies in Indonesia from time to time is not as simple as the general presupposition entails. This article shows that the development of hadith studies is raised following the provision of studies on ikhtilāf al-ḥadīth. The tradition of writing hadith in Indonesia began in the 17th century and, as a result, a number of hadith literatures have been produced by Indonesian Muslim scholars. This development challenges some scholars’ perception that the studies of hadith in Indonesia remain simple and the science of hadith in the country is hardly available.